Cytoskeletal regulation of synaptogenesis in a model of human fetal brain development. Issue 11 (26th July 2020) - Wilson, Emily; Rudisill, Taylor; Kirk, Brenna; Johnson, Colin; Kemper, Paige; Newell‐Litwa, Karen
Abstract: Excitatory synapse formation begins in mid‐fetal gestation. However, due to our inability to image fetal synaptogenesis, the initial formation of synapses remains understudied. The recent development of human fetal brain spheroids provides access to this critical period of synapse formation. Using human neurons and brain spheroids, we address how altered actin regulation impacts the formation of excitatory synapses during fetal brain development. Prior to synapse formation, inhibition of RhoA kinase (ROCK) signaling promotes neurite elongation and branching. In addition to increasing neural complexity, ROCK inhibition increases the length of protrusions along the neurite, ultimately promoting excitatory synapse formation in human cortical brain spheroids. A corresponding increase in Rac1‐driven actin polymerization drives this increase in excitatory synaptogenesis. Using STORM super‐resolution microscopy, we demonstrate that actomyosin regulators, including the Rac1 regulator, α‐PIX, and the RhoA regulator, p115‐RhoGEF, localize to nascent excitatory synapses, where they preferentially localize to postsynaptic compartments. These results demonstrate that coordinated RhoGTPase activities underlie the initial formation of excitatory synapses and identify critical cytoskeletal regulators of early synaptogenic events. Abstract : Graphical representation of presented data also showing RhoGTPase regulators that localize to nascent synapses.